1990
DOI: 10.1152/ajpregu.1990.259.1.r102
|View full text |Cite
|
Sign up to set email alerts
|

Role of aldosterone in angiotensin II-induced hypertension in rats

Abstract: Initial experiments demonstrated that a 1-h infusion of 10 ng/min angiotensin II (ANG II) into rats causes an increase in plasma aldosterone concentration (PAC) and that chronic administration of aldosterone alone to rats on increased sodium intake causes hypertension. We therefore hypothesized that a portion of the hypertensive effect of chronic ANG II infusion is accompanied by and dependent on chronic release of aldosterone. To test this hypothesis, 10 ng/min ANG II or saline was infused into chronically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Therefore, when ANG II was clamped, the progressive increase in body fluid volume and renal interstitial pressure became excessive (or inappropriate) to the existing plasma or renal levels of ANG II. The word inappropriate may be more pertinent because the hypertensinogenic effect of ANG II was produced in the presence of volume expansion that was not different from animals that did not receive ANG II and remained normotensive, although many other investigators have shown that increased sodium intake causes a marked potentiation of ANG II pressor effect (6,35,74,108,142,154). DeClue et al (36) was the first to demonstrate that a dissociation between extracellular fluid volume and the plasma or perhaps tissue levels of ANG II may be an important alteration underlying the development of high blood pressure.…”
Section: The Effects Of Sodium Intake On the Pressor Response To Ang IImentioning
confidence: 99%
“…Therefore, when ANG II was clamped, the progressive increase in body fluid volume and renal interstitial pressure became excessive (or inappropriate) to the existing plasma or renal levels of ANG II. The word inappropriate may be more pertinent because the hypertensinogenic effect of ANG II was produced in the presence of volume expansion that was not different from animals that did not receive ANG II and remained normotensive, although many other investigators have shown that increased sodium intake causes a marked potentiation of ANG II pressor effect (6,35,74,108,142,154). DeClue et al (36) was the first to demonstrate that a dissociation between extracellular fluid volume and the plasma or perhaps tissue levels of ANG II may be an important alteration underlying the development of high blood pressure.…”
Section: The Effects Of Sodium Intake On the Pressor Response To Ang IImentioning
confidence: 99%
“…[43][44][45] In view of the inhibitory effect of Ang II on renorenal reflexes, 5 it is interesting that arterial pressure is increased in response to long-term administration of a low dose Ang II when rats are fed an HNa but not an NNa diet. 46 The collective evidence suggests that under conditions of HNa intake, decreased activity of the afferent renal nerves results in development of increased arterial pressure to facilitate natriuresis as part of the overriding objective of maintaining sodium balance.…”
Section: Perspectivesmentioning
confidence: 99%
“…A calcium-dependent process is suggested by the ability of calcium entry blockers to prevent the rise of pressure. 31 Sodium retention may be important, but stimulation of the sodium-retaining steroid aldosterone by Ang II seems unimportant 27 - 34 ; there is less information on the direct sodium-retaining action of Ang II during the slow pressor response. In early experiments, Yu Also, infusion of Ang II at pressor doses in the dog 40 and at subpressor doses in humans 41 elicits no sign of sympathetic nerve activation.…”
mentioning
confidence: 99%